Synthesis of gold nanoparticles by various leaf fractions of Semecarpus anacardium L. tree - Raju, D.; Mehta, Urmil J.; Hazra, Sulekha (Trees-Structure and Function, 2011)
Gold nanoparticles (NPs) were synthesized using Semecarpus anacardium leaf extracts in water and the green biomass. Extract prepared at ambient condition by crushing the leaves in deionized water is identified as `green extract', and that by boiling the leaf pieces as `boiled extract'. The mass remaining after separating the `green extract' is identified as `green biomass'. These components triggered rapid reduction of Au(III) to Au (0) in HAuCl4 solution indicating the natural ability of the leaves of S. anacardium to synthesize NPs in ambient conditions. Green extract produced more NPs compared to the boiled extract suggesting denaturization of some of the useful factors due to boiling. NPs were quantified using UV and ICP-AES analysis. These were characterized using Transmission electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction. TEM images of the particles formed with green extract, boiled extract and green biomass showed that the particles were of different shapes and sizes.
Keywords: Biosynthesis; gold nanoparticles; Green extract; Semecarpus; TEM

Phytosynthesis of intracellular and extracellular gold nanoparticles by living peanut plant (Arachis hypogaea L.) - Raju, Dugyala; Mehta, Urmil J.; Ahmad, Absar (Biotechnology and Applied Biochemistry, 2012)
Inorganic nanomaterials of different chemical compositions are conventionally synthesized under harsh environments such as extremes of temperature, pressure, and pH. Moreover, these methods are eco-unfriendly and cumbersome, yield bigger particles, and agglomerate because of not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions, namely room temperature, atmospheric pressure, and physiological pH. These methods are reliable, eco-friendly, and cheap. In this paper, we report for the first time the extracellular and intracellular synthesis of gold nanoparticles (GNPs) using living peanut seedlings. The formed GNPs were highly stable in solution and inside the plant tissue. Transmission electron microscopy revealed that extracellular GNPs distributions were in the form of monodispersed nanoparticles. The nanoparticles ranged from 4 to 6 nm in size. The intercellular nanoparticles were of oval shape and size ranged from 5 to 50 nm. Both extracellular and intracellular nanoparticles were further characterized by standard techniques. The formed GNPs inside the plant tissue were estimated by inductively coupled plasma spectrometry. This opens up an exciting possibility of a plant-based nanoparticle synthesis strategy, wherein the nanoparticles may be entrapped in the biomass in the form of a film or produced in the solution, both of which have interesting applications.
Keywords: cells; extracellular; living plant; Peanut; root; TEM

Extra- and intracellular gold nanoparticles synthesis using live peanut callus cells - Raju, D.; Mehta, Urmil J.; Ahmad, Absar (Current Nanoscience, 2013)
An important challenge of considerable topical significance in nanotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials in large quantities with variable sizes, shapes and chemical compositions. Green synthesis routes for the production of inorganic metal nanoparticles using whole cell of microorganisms and plant extracts are gaining tremendous popularity as these are non-toxic, cheap and occur at ambient conditions. The present work emphasizes on gold nanoparticles synthesis protocol using live plant callus cells. Peanut callus cells when incubated with HAuCl4 solution in ambient conditions reduced the precursor and lead to formation of well dispersed, water soluble extracellular and intracellular gold nanoparticles within 24 hours. The biosynthesis of gold nanoparticles was monitored by UV-visible spectroscopy (UV-Vis) and further characterized by X-ray diffraction analysis (XRD), Energy Dispersive Spectroscopy (EDS) and Selected Area Electron Diffraction (SAED). The particle size distribution shows that the average particle size is 50 nm for extra-and 31 nm for intracellular gold nanoparticles. The nanoparticles may be stabilized by proteins secreted by callus cells. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, plant cell-based method for the synthesis of nanoparticles over a wide range of chemical compositions.
Keywords: Biosynthesis; callus; gold nanoparticles; live cells; Peanut; TEM

Phytosynthesis of silver nanoparticles by semecarpus anacardium L. leaf extract - Raju, D.; Hazra, Sulekha; Mehta, Urmil J. (Materials Letters, 2013)
Green synthesis of silver nanoparticles (AgNPs) using Semecmpus anacardium L leaf extract was studied. The reduction of silver (Ag+) ions was characterized by using UV-vis spectrophotometer showing formation of AgNPs within 15-20 mm. A time dependent reaction showed the increase in the nanoparticles (NPs) with time. Transmission electron microscopy (TEM) analysis showed that the synthesized AgNPs varied from 10 to 25 nm and has spherical shape. The Fourier transform infrared (FTIR) analysis showed that phenols and protein were responsible for the formation of the AgNPs. The energy dispersive spectroscopy (EDAX) analysis confirms the formed NPs were of silver. The quantification of AgNPs was studied by inductive coupled plasma spectrometry (ICP-AES). The important outcome of this work can be value addition to the medicinal plants in synthesis of NPs for biomedical applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: FTIR; Leaf extract; Nanoparticles; Semecarpus anacardium; synthesis; TEM

Biological synthesis of cationic gold nanoparticles and binding of plasmid DNA - Raju, D.; Vishwakarma, Rishi K.; Khan, Bashir Mohammad; Mehta, Urmil J.; Ahmad, Absar (Materials Letters, 2014)
Nanobiotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials. The present work focuses on synthesis of cationic gold nanoparticles (C-GNPs) for biological applications, especially in gene and drug delivery studies. A biosynthesis methodology has been developed for the functionalization of gold nanoparticles to cationic nature. The synthesis of C-GNPs was done by using peanut leaf extract in the presence of cysteamine. The formed C-GNPs were characterized by using UV-visible spectroscopy (UV-vis), the particles sizes and shapes were confirmed by a Transmission electron microscope (TEM) and crystallinity of C-GNPs was characterized by diffraction. The binding of plasmid DNA on the C-GNPs was confirmed by agarose gel electrophoresis. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Cationic; Nanoparticles; Plasmid DNA; synthesis; TEM

Extracellular synthesis of silver nanoparticles using living peanut seedling - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Applied Nanoscience, 2014)
Synthesis of nanoparticles by environment friendly method is an important aspect of nanotechnology. In the present study, extracellular reduction of silver ions to silver nanoparticles was carried out using living peanut plant. The electron microscopic analysis shows that the formed nanoparticles were of different shapes and sizes. The formed nanoparticles were polydispersed. The shapes of the nanoparticles were spherical, square, triangle, hexagonal and rod. Most of the particles were spherical and 56 nm in size. EDS analysis confirmed the formed nanoparticles were of silver. The crystalline nature of nanoparticles was confirmed by diffraction. This method opens up an exciting possibility of plant-based synthesis of other inorganic nanomaterials. This study confirms the synthesis of extracellular silver nanoparticles by living plant.
Keywords: Nanoparticles; Shapes; Silver; synthesis; TEM

Living plant-mediated synthesis of different shaped gold nanoparticles - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Nanoscience and Nanotechnology Letters, 2014)
We demonstrate extracellular green synthesis of gold nanoparticles with different shapes and sizes by using live Prosopis juliflora L. seedling. The conversion of ionic to metallic gold nanoparticles by P. juliflora seedling was carried out in short period. The formed nanoparticles were characterized by UV, TEM, Diffraction and EDS. TEM shows well dispersed particles of different shapes and sizes. The percentage of different shapes of nanoparticles was calculated, most of the particles were spherical in shape (75%). The triangle nanoparticles were 10%, followed by squares (8%), hexagonal (5%) and rods (2%). The diffraction shows the formed nanoparticles are crystalline in nature and EDS confirms the formed nanoparticles are of gold. This shows P. juliflora seedling can synthesis different shapes of well dispersed nanoparticles.
Keywords: Gold; Nanoparticles; Prosopis juliflora; Shapes; synthesis; TEM